High-Accuracy Linearity Measurement of Broadband Frequency Chirps - Bent Walther; Andre Froehly; Thomas Musch; Marcel van Delden (IEEE Open Journal of Instrumentation and Measurement)
High-resolution radar systems use fast and broadband frequency chirps to enable high resolutions with short measurement times. One challenge in these radar systems is minimizing the linearity error in the generated frequency chirps, directly influencing the achievable depth resolution and precision. Current measurement methods cannot meet the bandwidth requirements of modern chirp generators, making it difficult to determine the linearity error precisely. For this reason, we present a novel measurement method that uses a frequency divider to enable linearity measurements with very high accuracy using conventional measurement equipment. Since frequency dividers generate additional artifacts, such as harmonics, we present a novel correction algorithm to prevent these artifacts in the measurement results. The algorithmic framework utilizes a virtual digital frequency chirp to detect RMS frequency errors in the sub-Hz range unprecedentedly. Furthermore, the influence of the frequency divider is systematically characterized, enabling precise correction of its contributions to the measurement results. This method improves the accuracy of chirp linearity measurements and allows for the characterization of current linearity measurement systems. The approach was validated through experimental measurements, even under noise, aliasing, and harmonic conditions.